2005
DOI: 10.1128/jvi.79.1.277-288.2005
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Complete Rhinovirus RNA Polymerase Suggests Front Loading of Protein Primer

Abstract: Picornaviruses utilize virally encoded RNA polymerase and a uridylylated protein primer to ensure replication of the entire viral genome. The molecular details of this mechanism are not well understood due to the lack of structural information. We report the crystal structure of human rhinovirus 16 3D RNA-dependent RNA polymerase (HRV16 3D pol ) at a 2.4-Å resolution, representing the first complete polymerase structure from the Picornaviridae family. HRV16 3D pol shares the canonical features of other known p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Consistently, mutation of Leu-30 to Ser or Arg results in an inactive enzyme (33). Helical regions at the tip of fingertip loops connecting the fingers and thumb are present in other viral RdRps (12)(13)(14)(15)(16)(17)19). The similarities in the structure and enzymatic mechanism (34) between NS5B and these polymerases suggest that flexibility of the fingertip loops could also be a feature of some of these RdRps, and inhibitor binding sites similar to the one described here could also be available for them.…”
Section: Indole-based Nnis and Other Small Molecule Bindingmentioning
confidence: 58%
See 1 more Smart Citation
“…Consistently, mutation of Leu-30 to Ser or Arg results in an inactive enzyme (33). Helical regions at the tip of fingertip loops connecting the fingers and thumb are present in other viral RdRps (12)(13)(14)(15)(16)(17)19). The similarities in the structure and enzymatic mechanism (34) between NS5B and these polymerases suggest that flexibility of the fingertip loops could also be a feature of some of these RdRps, and inhibitor binding sites similar to the one described here could also be available for them.…”
Section: Indole-based Nnis and Other Small Molecule Bindingmentioning
confidence: 58%
“…As a result, the polymerase has a relatively closed and spherical appearance, and the active site cavity, to which the RNA template and the NTP substrates have access via two positively charged tunnels, is completely encircled. Structural studies have shown that other viral RdRps, such as those of poliovirus (12,13), human rhinovirus (14,15), bovine viral diarrhea virus (16), rabbit hemorrhagic disease virus (17), reovirus (18), and bacteriophage 6 (19), have the same global architecture and a similar closed conformation. Crystal structures of NS5B bound to a short RNA template or to NTPs have also been solved (20,21).…”
Section: The Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…K276 is located at the top of the middle finger and is near the RNA template entry channel, but it does not directly interact with the RNA in any of the picornaviral 3D pol -RNA complexes whose structures have been solved thus far. The structural orientations of the phylogenetically conserved amino acids implicated in the polyadenylation of viral RNA are similar in the atomic structures of 3D pol of enterovirus 71 (35), a group A enterovirus; 3D pol of coxsackievirus B3 (36,37), a group B enterovirus; 3D pol of poliovirus (13,16), a group C enterovirus; 3D pol of rhinovirus type 16 (38,39), species A; 3D pol of rhinovirus type 14 (39), species B; and foot-and-mouth disease virus 3D pol (40,41). These phylogenetically conserved sequences and structures likely contribute to the reiterative transcription of poly(A) and poly(U) sequences during viral RNA replication in these other picornaviruses as well, thereby regulating the lengths of poly(A) at the 3= end of viral RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the VPg-binding site on 3D pol , two different sites seem to coexist. The first complete crystal structures of Picornaviridae RdRps of various human rhinovirus (HRV) strains (1,32) showed a widely open access to the active site from the "front" of the RdRp. Accordingly, a model was proposed that accommodated the VPg primer in a "frontloading" position (1).…”
mentioning
confidence: 99%
“…The first complete crystal structures of Picornaviridae RdRps of various human rhinovirus (HRV) strains (1,32) showed a widely open access to the active site from the "front" of the RdRp. Accordingly, a model was proposed that accommodated the VPg primer in a "frontloading" position (1). This was indeed demonstrated by the crystal structure of the FMDV RdRp in complex with VPg-pU (12).…”
mentioning
confidence: 99%